Preparation of IT Disaster Recovery Plan (DRP) using NIST SP 800-34 Framework (Case Study: PT Pamapersada Nusantara, Jakarta) - Erma Dearniwati; Gusti Ahmad Nurlette; Saiful Anwar; Heru Purwanto (Eduvest - Journal of Universal Studies, 2025)
Information Technology (IT) in the industrial world is an important part in the development of business processes and plays a vital role, including for PT Pamapersada Nusantara. To maintain the continuity of its business process activities, PT Pamapersada Nusantara is aware of the need for continuous control. This control effort is closely related to the increased risk from the application of information technology. Risks that have a negative impact have the potential to threaten the sustainability of the organization's business activities if they reach certain criteria, making it a disaster. This has prompted PT Pamapersada Nusantara to prepare for the possibility of a disaster. The purpose of this activity is to prepare an IT Disaster Recovery Plan (DRP). DRP is a type of contingency plan that includes the preparation and response of an organization in the event of a disaster. The preparation of this DRP is guided by the NIST SP 800-34 framework, which begins with risk identification and assessment, Business Impact Analysis (BIA), identification of preventive controls and preparation of contingency strategies. After these steps have been taken, it is continued with the development of a contingency plan which includes plans for the activation phase, recovery phase and reconstitution phase. The result of this activity is a DRP document that is adapted to the organizational conditions of PT Pamapersada Nusantara. This DRP document contains a service recovery guide along with preventive measures before a disaster occurs. Keywords : disaster, risk, disaster recovery plan, NIST SP 800-34.